Clinical, radiology, pathologic patterns and outcomes of vaping related pulmonary injury in a single institution; A case series. (November 2020) - Kaous, Maryam; Xian, Jonathan; Rongo, Daniel; McDonald, Michelle; Ocasionez, Daniel; Mathew, Reeba; Estrada -Y- Martin, Rosa M.; Patel, Bela; Cherian, Sujith V.; Jani, Pushan P.
Abstract: Since March 2019, E-cigarette or Vaping product associated lung injury (EVALI) has become an ongoing epidemic with more 2600 cases reported in the span of a few months in the United States. EVALI is defined as acute lung injury that develops secondary to the use of e-cigarettes or vaping products within the previous 90 days after exlusion of other possible inciting factors. Vitamin E acetate is believed to play a significant role in its pathogenesis. Treatment involves use of corticosteroids and further avoidance of these products. We describe a case series of 8 patients with EVALI, their clinical course and outcomes. All patients showed an excellent response to corticosteroids. In our experience, prognosis of EVALI is excellent, with complete resolution of symptoms in patients who followed up at 8 weeks. Highlights: EVALI is a public health hazard. Lung injury pattern can be seen with as little as one week exposure even in an otherwise healthy young population. Lipid laden macrophages on BAL may be evident, though not pathognomonic. May see a subpleural sparing pattern and ground glass opacities on radiologic imaging. Steroids may play a role in symptom resolution.